Zooplankton variation in relation to hydrology in an enclosed hypoxic bay (Amvrakikos Gulf, Greece) - KEHAYIAS, G.; APOSPORIS, M. (Mediterranean Marine Science, 2014)
This study investigated the temporal and spatial variation of the zooplankton community of a hypoxic coastal embayment (Amvrakikos Gulf, western Greece) in relation to hydrological characteristics during an annual cycle. The main hydrological feature was the prolonged water stratification, which determined hypoxic conditions in the deeper layers that became anoxic close to the bottom in September, while vertical mixing occurred for a very short period (October-November). The total zooplankton abundance fluctuated between 44.6 and 159.7 ind l-1. Fourteen groups were recorded, among which copepods dominated accounting on average for 86.4 %. Most of the groups presented higher abundance values in winter and spring when increased chlorophyll-α concentrations were found. Oxygen depletion affects the vertical distribution of most zooplankton groups and the vertical habitat partitioning between copepod orders and their ontogenetic stages. Several taxa were recorded even in the deep, anoxic layers, but only the polychaete larvae increased in abundance with depth. Calanoids, appendicularians and bivalve larvae presented eastward decrease of abundance in the deepest layers following the same pattern of oxygen decrease. Notwithstanding hypoxic conditions in its deepest layers, Amvrakikos Gulf was accounted for a mesotrophic ecosystem, with the nutrient concentration being lower than in the past. Several biotic elements indicate that the gulf is in a transitional phase towards a better quality state and these results reinforce the need for consistent monitoring of this ecosystem.